2023
DOI: 10.1002/adfm.202301372
|View full text |Cite
|
Sign up to set email alerts
|

Stress‐Triggered Mechanoluminescence in ZnO‐Based Heterojunction for Flexible and Stretchable Mechano‐Optics

Abstract: Owing to the forthcoming global energy crisis, the search for energy‐saving materials has intensified. Over the past two decades, mechanically induced luminescent materials have received considerable attention as they can convert waste into useful components, for instance, the conversion from stress into light. However, this material features many constraints that limit its widespread application. Herein, a strategy to improve the mechanoluminescence (ML) of ZnO by embedding it in a ZnF2:Mn2+ matrix is introdu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 28 publications
(9 citation statements)
references
References 58 publications
0
9
0
Order By: Relevance
“…According to the data, when Dq/ B > 2.3, the main body is a strong crystal field and 2 E → 4 A 2 of Cr 3+ ions dominates. 35–37 At this point, the NIR light exhibits narrowband emission. When Dq/ B < 2.3, indicating a weak crystal field, a 4 T 2 → 4 A 2 transition occurs, leading to broadband emission.…”
Section: Resultsmentioning
confidence: 99%
“…According to the data, when Dq/ B > 2.3, the main body is a strong crystal field and 2 E → 4 A 2 of Cr 3+ ions dominates. 35–37 At this point, the NIR light exhibits narrowband emission. When Dq/ B < 2.3, indicating a weak crystal field, a 4 T 2 → 4 A 2 transition occurs, leading to broadband emission.…”
Section: Resultsmentioning
confidence: 99%
“…The results indicated that the emitted light intensity and applied stress exhibited a linear relationship, implying that ZnGa 2 S 4 : Mn 2+ can be used as a stress detection sensor, robotic tactile, and intelligent anti‐counterfeiting in diverse realms. [ 2,31,6,32 ] Figure S7, Supporting Information, shows the ML intensity of ZnGa 2 S 4 : 5% Mn synthesized by molten salt shielding method and traditional solid phase method respectively, which means the molten salt method is able to enhance the ML intensity of ZnGa 2 S 4 phosphor. The ML images under different light conditions are shown in Figure S6, Supporting Information, of the supporting material.…”
Section: Resultsmentioning
confidence: 99%
“…Usually, counterfeit goods will use inferior products or even contain toxic and harmful raw materials, which seriously jeopardize people’s health and disrupt the market order. As a result, various anticounterfeiting technologies have emerged, such as radio frequency technology, laser holograms, and watermarks. However, most of these technologies require a high cost and complex equipment. Therefore, low-cost and easy-to-implement screen printing technology has gradually attracted people’s attention.…”
Section: Introductionmentioning
confidence: 99%